APPLICATION OF BIOHERBICIDES BASED ON FERN TREE (Filicium decipiens) AND MAHOGANY (Swietenia macrophylla) LEAVES AGAINST COGON GRASS (Imperata cylindrica) WEED - Rini, Dwi Nur Puspita; Riniarti, Melya; Duryat, Duryat; Asmarahman, Ceng (Gorontalo Journal of Forestry Research, 2025)
Imperata cylindrica is an aggressive and difficult-to-control weed in production forest areas. The use of plant-based bioherbicides offers an environmentally friendly alternative to reduce reliance on synthetic herbicides. This study aims to evaluate the effectiveness of extracts from Filicium decipiens and Swietenia macrophylla in suppressing the growth of weeds. The study was conducted using a Competly Randomized Design with five treatments: control, 25% and 50% F. decipiens extract, and 25% and 50% mahogany extract, and replicated 5 times. The parameters observed included changes in leaf color, survival rate, root length and diameter. The results showed that the 50% F. decipiens extract was most effective in reducing root diameter and plant survival rate (only 20% survived), while the 50% mahogany extract most effectively inhibited root length. The browning of leaves indicated tissue damage caused by phenolic compounds, flavonoids, and saponins. This study demonstrated that F. decipiens leaf and mahogany extracts have potential as effective and environmentally friendly bioherbicides for controlling sedge weeds.